Beyond the catwalk: Designing fashion shows between the ephemeral and responsibility - Franzo, Paolo (Convergences - Journal of Research and Arts Education, 2025)
Fashion shows have been the subject of increasing critical attention for their environmental and symbolic impact, resulting emblematic of the contradictions of contemporary spectacular capitalism. While originally they were functional moments for the presentation of seasonal collections, today they are configured as real artistic productions with a high consumption of resources, often organised in exotic or symbolic places, with a significant ecological footprint. However, since the Covid-19 pandemic, there has been an intensification of reflection on the organisational methods and transformative potential of these events. This article analyses three emerging approaches that show concrete attempts to reconfigure fashion shows in an ecological and sustainable way: the use of nature as a performative setting, the aestheticisation of waste and the promotion of circularity. Through the critical analysis of case studies – from the fashion shows immersed in nature by Marine Serre and Jacquemus, to the use of recycled materials by Marni and Diesel, to the reuse and conscious design policies promoted by Bureau Betak, Prada and Spazio Meta – both the expressive potential and the structural limits of these practices are highlighted. In particular, the article emphasises how the sustainability of fashion shows cannot be addressed only as a technical issue, but implies a cultural, aesthetic and political rethinking of the very role of fashion within contemporary society. Fashion shows thus become not only brand communication tools, but also performative spaces in which new relationships between creativity, environment and cultural production are negotiated.